ANTICANCER DRUGS AS POTENTIAL INHIBITORS OF AcrAB-TolC OF MULTIDRUG RESISTANT E.coli: AN IN SILICO MOLECULAR MODELING AND DOCKING STUDY - Gupta, Pranjali; Rai, Nishant; Gautam, Pankaj (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: Overexpression of AcrAB-TolC protein complex is often associated with the virulence of multidrug-resistant bacteria. Development of an effective efflux pump inhibitors (EPI) can be a major strategy to enhance the effectivity of current antibiotics and to restrain the menace of antibiotic resistance among bacteria. Molecular docking based assessment of anticancer drugs as EPI with comparable docking scores of known putative EPI. Methods: Molecular docking of target proteins (AcrA, AcrB and TolC) of Escherichia coli was carried out with four putative and seven selected anticancer drugs using iGEMDOCK software separately. Results: All the four putative inhibitors (norepinephrine, reserpine, verapamil and trimethoprim) used in the present study binds to AcrA (âˆ’41.9 kcal/mol, âˆ’56.75 kcal/mol, âˆ’76.69 kcal/mol and âˆ’45.20 kcal/mol respectively), AcrB (âˆ’74.61 kcal/mol, âˆ’135.97 kcal/mol, âˆ’126.66 kcal/mol and âˆ’87.57kcal/mol respectively) and TolC (âˆ’78.49 kcal/mol, âˆ’90.22 kcal/mol, âˆ’89.42 kcal/mol and âˆ’62.57 kcal/mol respectively) with high affinity and seven drug ligands (etoposide, paclitaxel, tamoxifen, mitomycin and thalidomide, vinblastine methotrexate) showed comparable docking energies (AcrA [âˆ’36.44 kcal/mol, âˆ’78.23 kcal/mol, âˆ’17.04 kcal/mol, âˆ’42.96 kcal/mol, âˆ’44.94 kcal/mol, âˆ’67.96 kcal/mol and âˆ’20.15 kcal/mol respectively], AcrB [âˆ’128.11 kcal/mol, âˆ’132.86 kcal/mol, âˆ’104.85 kcal/mol, âˆ’98.91 kcal/mol, âˆ’96.47 kcal/mol, âˆ’108.79 and âˆ’106.36 kcal/mol respectively], TolC [âˆ’68.42 kcal/mol, âˆ’88.29 kcal/mol, âˆ’64.69 kcal/mol, âˆ’68.28 kcal/mol, âˆ’59.36 kcal/mol, âˆ’77.28 kcal/mol and âˆ’74.52 respectively]) with putative inhibitors. Conclusion: Paclitaxel and vinblastine showed high affinity for all units of AcrAB-TolC of E. coli. Keywords: AcrAB-TolC, Efflux pump, Efflux pump inhibitor, Multidrug resistance, Molecular modeling and docking, Escherichia coli.